Imaging a Wide Swath with Full Polarimetry - Villano, Michelangelo; Papathanassiou, Konstantinos P.; Krieger, Gerhard; Moreira, Alberto (Polarimetric and Interferometric SAR Workshop (PI-SAR), 2015)
Several applications of synthetic aperture radar (SAR) require or at least benefit from full polarimetry. In the past, however, full polarimetry has been often discarded in the design of spaceborne SAR missions, as it implied a significant reduction of the swath width, already constrained by the requirement on azimuth resolution. Innovative SAR techniques, based on digital beamforming on receive, allow nowadays high-resolution wide-swath (HRWS) imaging through multiple elevation beams, which simultaneously map multiple sub-swaths. Furthermore, a continuous variation of the pulse repetition interval, i.e., staggered SAR, can be introduced to get rid of the ``blind ranges″ between the multiple sub-swaths, due to the fact that the radar cannot receive, while it is transmitting. This paper considers how the introduction of full polarimetry in HRWS imaging makes the design of the SAR system more challenging, but represents a viable solution for frequent and seamless high-resolution fully-polarimetric imaging of the Earth′s surface.
DLR Import::2019-04-03